Development strategy of human resource competency in the preservation field - Sudiarti, Leni; Hamka; Rivai, Firman Hadi (Record and Library Journal, 2023)
Background of the study: The Center for Preservation and Media Transfer of Library Materials of the National Library of Indonesia (PNRI) is also responsible for restoring various types of collections. It is necessary to increase and develop competence in handling these collections, considering the various conditions and types of library materials. Preservation of the physical and information needed to make the collection last longer. Purpose: To formulate the strategies for improving and developing the competence of preservation human resources in this unit. Findings: Based on the SWOT analysis, this unit is in quadrant I, meaning that it has great strengths and opportunities to improve and develop competencies. The recommended strategies are: a) facilitating staffs to gain knowledge through education, training, comparative studies, workshops and other conservation events, b) facilitating Preservation Human Resources certification, c) development of managerial and sociocultural competencies, for Head of Working Group, Sub Head of Working Group and staff who are also members of the facilitators/teachers, d) establish various preservation SOPs, e) work closely with the Education and Training Center to accommodate preservation staff training needs, f) create plans for improving and developing well-structured resources, g) sharing knowledge independently among preservation staff. h) Massive socialization of Preservation Performance Competency Standards (SKKNI) to preservation human resources, so that the standards can become a reference for preservation human resources in their work. Conclusion: Competency improvement and development is needed so that preservation activities at the National Library of Indonesia can run even better, so that they can be more beneficial in society.